Probable transient antiphospholipid syndrome - Tsompos, Constantinos (Medicinski časopis, 2013)
The event of at least one of the following two clinical findings (either vascular thrombosis or obstetric complication) and one of the following two laboratory findings (either positive lupus anticoagulant or β2-glycoprotein I IgG antibodies title or anticardiolipin IgM antibodies increase) in two different measurements, set the diagnosis of antiphospholipid syndrome. Fetal demise is defined the unlucky situation that happens after 34 weeks of gestation age, with neither clear laboratory findings nor reasons. Interest is presented when a clinical finding is combined with an informal laboratory finding.